5-HTTLPR and STin2 polymorphisms in the serotonin transporter gene and irritable bowel syndrome: effect of bowel habit and sex - Niesler, Beate; Kapeller, Johannes; Fell, Catherine; Atkinson, Wendy; Möller, Dorothee; Fischer, Christine; Whorwell, Peter; Houghton, Lesley A. (European journal of gastroenterology & hepatology, 2010)
Background - Conflicting data exist on the association between functional polymorphisms in the serotonin reuptake transporter (SERT) gene (SLC6A4) and irritable bowel syndrome (IBS). This may be partly because of small participant numbers and varying ethnic origin and sex within the cohorts studied. - Aim - To reassess the potential association between the SERT polymorphisms 5-HTTLPR and STin2 in both male and female IBS patients with diarrhoea (IBS-D) and constipation (IBS-C) compared with healthy volunteers. - Methods - In this case-control study, 196 Caucasian Rome II IBS patients [97 IBS-D (aged 18-66 years; 67 female) and 99 IBS-C (aged 18-65 years; 95 female)] and 92 Caucasian healthy volunteers (aged 18-63 years; 60 female) from the UK had genomic DNA extracted from peripheral blood and the 5-HTTLPR and STin2 polymorphisms genotyped. - Results - The frequency of the 5-HTTLPR (ss) genotype was slightly lower in both IBS-D (16.5%) and IBS-C (14.3%) patients compared with controls (23.9%), although not significantly (P≤0.191). This seemed to be related to a reduction in the frequency of the 5-HTTLPR (ss) genotype in male patients, particularly those with IBS-D [IBS-D 10%, IBS-C 25%, controls 37.5%; P=0.01 for IBS-D vs. controls; odds ratio (95% confidence interval) for 5-HTTLPR (ss) vs. 5-HTTLPR (non-ss)=0.185 (0.046-0.744)] than in female patients (IBS-D 19.4%, IBS-C 13.8%, controls 16.7%). There were no differences in the frequencies of either the 5-HTTLPR (ll) or (ls), or STin2 genotypes between any of the three groups. - Conclusion - Our finding that male IBS-D patients have a reduced frequency of the 5-HTTLPR (ss) genotype contradicts three earlier studies of a similar size, which did not take sex into account. Therefore, replication studies in even larger cohorts, stratifying for sex and endophenotypes, after assessing physiological and psychological traits, are required to unravel the contribution of SERT polymorphisms to the IBS phenotype.